The Effectivity of “Beta Pulih” Program to Reduce Negative Emotions of Juvenile Offenders - Manafe, Rizky Pradita; Benu, Juliana Marlin Yusrianti (Psikodimensia: Kajian Ilmiah Psikologi, 2024)
Interventions related to forgiveness have a positive impact on individuals' positive emotions. Forgiveness is important for victims who experience bitterness. There is still little research that discusses forgiveness among juvenile offenders. Juvenile offenders are 'victims' of other offenders, thus causing juvenile offenders have negative emotions towards other people and themselves. The aim of this research is to know effectivity of 'Beta Pulih' program to help juvenile offenders reduce negative emotions. The Beta Pulih program is designed based on Enright's forgiveness process. The design of this research is quasi-experimental with a one group pretest-posttest design. Participants were selected using random sampling from children detention center in Kupang. The number of participants was 16 people. Participants take the program for four sessions. The research results show that the Beta Pulih Program can reduce the negative emotions of juvenile offenders with a value of t = 9,188 and a significance of 0.000, which shows that there is a difference in negative emotions before and after the program is implemented. Juvenile offenders are also aware of the hurt they are experiencing, but find it difficult to express positive emotions in an adaptive way. The implication of this research is to design private sessions with juvenile offenders to help juvenile offenders be able to express positive emotions.